2018
DOI: 10.1021/acs.jpclett.8b02363
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Hydrogen Gas Environment-Promoted Nanostructural Changes in Stressed and Relaxed Palladium by Environmental Transmission Electron Microscopy and Variable-Energy Positron Annihilation Spectroscopy

Abstract: Environmental transmission electron microscopy (ETEM) and variable-energy positron annihilation spectroscopy (VEPAS) are used to observe hydrogen-induced microstructural changes in stress-free palladium (Pd) foils and stressed Pd thin films grown on rutile TiO substrates. The microstructural changes in Pd strongly depend on the hydrogen pressure and on the stress state. At room temperature, enhanced Pd surface atom mobility and surface reconstruction is seen by ETEM already at low hydrogen pressures ( p < 10 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…However, changes of the S parameter are found in the Pd over-layer (E < 13 keV). This effect is discussed by Roddatis et al [16].…”
Section: Appendix A: Variable Energy Positron Annihilation Spectrosco...mentioning
confidence: 80%
See 1 more Smart Citation
“…However, changes of the S parameter are found in the Pd over-layer (E < 13 keV). This effect is discussed by Roddatis et al [16].…”
Section: Appendix A: Variable Energy Positron Annihilation Spectrosco...mentioning
confidence: 80%
“…Metal/oxide systems using titanium dioxide (TiO 2 ) as a support have been used in a broad range of technological applications where they serve as model systems for fundamental process studies in surface science [1,2], catalysis [3][4][5][6][7][8][9][10][11][12][13][14][15][16], the field of resistive switching [17][18][19], as well as for Schottky contacts [20][21][22][23]. One central question in these studies is how chemical and physical properties of the metal/TiO 2 interface are influenced by an electric field [19], by metal-support interaction [11], or by defect concentrations [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Although very little microscopy work has been done on fcc metals implanted with He at cryogenic temperatures, He bubble formation has been studied in aged Pd tritide, PdT 0.6 . Tritium decay does not induce displacement damage in the lattice, so the vacancy concentration is limited to thermal vacancies, although H can stabilize vacancies, and formation of β-phase hydride can cause microstructural changes [18]. Bubbles are at equilibrium when the He pressure inside the bubble equals the surface tension of the host material, p = 2 γ / r , where p is the He pressure, γ is the surface energy of the host material, and r is the bubble radius [19].…”
Section: Discussionmentioning
confidence: 99%
“…A previous work has found that H dopants in metal oxide materials may promote the aggregation and migration of oxygen vacancies. 27,36 Therefore, we expect that in H−VO 2−δ the effusion of hydrogen dopants upon environmental heating could drive the removal of interior V O defects. Here we simulated the migration of V O in a 2 × 2 × 2 VO 2−δ supercell with or without H-doping by using the Climbing-Image Nudge Elastic Band (CI-NEB) method to locate the transition states along the V O migration pathway.…”
mentioning
confidence: 99%